2015
DOI: 10.1021/acs.nanolett.5b01505
|View full text |Cite
|
Sign up to set email alerts
|

Highly Sensitive and Stretchable Multidimensional Strain Sensor with Prestrained Anisotropic Metal Nanowire Percolation Networks

Abstract: To overcome the limitation of the conventional single axis-strain sensor, we demonstrate a multidimensional strain sensor composed of two layers of prestrained silver nanowire percolation network with decoupled and polarized electrical response in principal and perpendicular directional strain. The information on strain vector is successfully measured up to 35% maximum strain with large gauge factor (>20). The potential of the proposed sensor as a versatile wearable device has been further confirmed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
436
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 572 publications
(441 citation statements)
references
References 37 publications
3
436
2
Order By: Relevance
“…In recent years, several studies have reported highly flexible and stretchable micro- and nanostructured pressure and strain sensors based on polymers embedded with electrically active materials such as silver or gold nanowires (AgNW or AuNW) 6,7,11,12 , carbon nanotubes 9,1321 (CNT), graphene 22–26 , graphite 24–26 , and other materials including inherently conducting polymers 1,35,10,2734 . Achieving large stretchability (ɛ > 50%) and a high sensitivity (GF > 100) with a wide detection range have been the key factors in the development of strain sensors.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, several studies have reported highly flexible and stretchable micro- and nanostructured pressure and strain sensors based on polymers embedded with electrically active materials such as silver or gold nanowires (AgNW or AuNW) 6,7,11,12 , carbon nanotubes 9,1321 (CNT), graphene 22–26 , graphite 24–26 , and other materials including inherently conducting polymers 1,35,10,2734 . Achieving large stretchability (ɛ > 50%) and a high sensitivity (GF > 100) with a wide detection range have been the key factors in the development of strain sensors.…”
Section: Introductionmentioning
confidence: 99%
“…. As an alternative material, silver nanowires (AgNWs) have been of great interest [25][26][27][28][29][30][31][32][33][34][35][36][37][38] due to the ability to form highly conductive percolative networks. [38][39][40][41] AgNW based sensing composite materials, formed exclusively by layer deposition, consist of a percolative network of the nanowires adhered to a flexible polymer substrate.…”
mentioning
confidence: 99%
“…Recently, flexible sensors have attracted increasing attention due to their great potential applications in wearable electronics and intelligent systems [1][2][3][4][5][6][7][8][9][10]. Particularly, flexible sensors can be mounted on human body or clothing for continuously monitoring subtle and large human motions [11][12][13][14] and physiological information, such as phonation [15], pulse [16][17][18], electrocardiogram (ECG) [19][20][21], respiration [22,23], skin temperature [24,25], and so on. Towards these applications, wearable sensors should have some basic characteristics, such as high sensitivity, good flexibility, desirable stretchability, biocompatibility and good stability.…”
Section: Introductionmentioning
confidence: 99%